2007
DOI: 10.1088/0964-1726/16/2/s07
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical actuation of carbon nanotube yarns

Abstract: We report on actuation in high tensile strength yarns of twist-spun multi-wall carbon nanotubes. Actuation in response to voltage ramps and potentiostatic pulses is studied to quantify the dependence of the actuation strain on the applied voltage. Strains of up to 0.5% are obtained in response to applied potentials of 2.5 V. The dependence of strain on applied voltage and charge is found to be quadratic, in agreement with previous results on the actuation of single-wall carbon nanotubes, with the magnitude of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 14 publications
2
95
0
1
Order By: Relevance
“…Electrostatic attraction and repulsion between two nanotubes have been used for cantilever-based nano-tweezers 101 and mechanically based switches and logic elements. 102,103 On the macroscale, electrically powered [104][105][106][107][108][109][110][111] and fuel-powered 112,113 electrochemical carbon nanotube actuators provide up to a few percent actuator stroke and over a hundred times higher stress generation than natural muscle. Large-stroke pneumatic nanotube actuators have been demonstrated that use electrochemical gas generation within nanotube sheets.…”
Section: Carbon Nanotube-based Artificial Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrostatic attraction and repulsion between two nanotubes have been used for cantilever-based nano-tweezers 101 and mechanically based switches and logic elements. 102,103 On the macroscale, electrically powered [104][105][106][107][108][109][110][111] and fuel-powered 112,113 electrochemical carbon nanotube actuators provide up to a few percent actuator stroke and over a hundred times higher stress generation than natural muscle. Large-stroke pneumatic nanotube actuators have been demonstrated that use electrochemical gas generation within nanotube sheets.…”
Section: Carbon Nanotube-based Artificial Musclesmentioning
confidence: 99%
“…104 Using more recently available highly oriented carbon nanotube yarns that have much higher modulus and strength, this actuation stress was increased to 26 MPa, which is nearly a hundred times that of natural muscle. 107,108,126 This stress generation capability (whose product with the muscle cross-sectional area determines the maximum weight that an initially unloaded muscle can lift) is still far below the ultimate potential of carbon nanotube artificial muscles, which could be achieved by increasing the modulus of carbon nanotube yarns to close to that of the individual carbon nanotubes. Using the ~0.2% strain that is typically observed for carbon nanotube yarns and sheets 108 and a 640 GPa Young's modulus, 126 an isometric stress generation capability potentially of 1.3 GPa (which is the product of the strain and modulus) could be generated by SWNT actuators, which is about 4000 times higher than that of natural muscle.…”
Section: Carbon Nanotube Muscles Based On Electrical or Chemical Doubmentioning
confidence: 99%
See 1 more Smart Citation
“…However, technical challenges have limited the development of strong, flexible and weavable yarns and fibres having attractive supercapacitor performance. Previously developed yarn supercapacitors have been based on solution-spun CNT/ polymer fibres 17 and dry-spun CNT fibres 18 , which have lower energy storage capabilities than redox materials such as conducting polymers and metal oxides.…”
mentioning
confidence: 99%
“…The second only requires a few Volts to operate but suffer from low electromechanical coupling (Bar-Cohen et al, 2007). Examples of EAP's are Dielectric elastomers (DE) (Chuc et al, 2009), and Carbon nanotubes (Mirfakhrai et al, 2007).…”
Section: Control and Actuationmentioning
confidence: 99%